Technological characterization of engineered panels produced with paricá wood (Research, Society and Development, 2020)
The demand for wood-based products is growing, mainly from planted forests. In this way it is possible to maximize the use of wood and obtain products with resistance and reliability of use. The objective was to study the technological properties of plywood and Laminated Veneer Lumber (LVL) produced with paricá wood (Schizolobium amazonicum Huber ex Ducke). Water absorption, density (basic and apparent), humidity, porosity, thickness swelling and residual swelling were evaluated. 30 specimens of each type of panel were used, the data were analyzed using descriptive statistics and Pearson's correlation matrix. In the plywood, the basic density, bulk density and porosity were 0.38 g cm-3, 0.44 g cm-3 and 75.47%, respectively. Still, the humidity rose 20.91% between 2 and 96 hours of immersion in water. The residual swelling was 3.75% and the thickness swelling increased by 0.81% between 2 and 96 hours of immersion. In LVL, the basic density (0.41 g cm-3) and the apparent density (0.48 g cm-3) were higher in relation to the plywood and the porosity was lower. The residual swelling (4.24%) and the increase in thickness swelling (1.22%) were higher than the plywood. Due to their high hygroscopicity, the applications of the panels evaluated should preferably be in environments without contact with humidity.